Atuação do psicólogo nos núcleos de acessibilidade das universidades federais brasileiras - Ciantelli, Ana Paula Camillo; Leite, Lúcia Pereira; Nuernberg, Adriano Henrique (My University, 2017)
Public and institutional actions guide the access and permanence of the person with disabilities in Higher Education. The Programa Incluir - Acessibilidade na Educação Superior [To Include Program - Accessibility in Higher Education] aims at developing institutional policies of accessibility at the Instituições Federais de Ensino Superior - IFES [Federal Institutions of Higher Education], in order to academically develop disabled students and/or those with reduced mobility. Among those actions there is the creation and consolidation of accessibility centers. This study aims at identifying and discussing the role of Psychology in these centers, paying special attention to how it's coordinators act throughout this process. 17 center coordinators from those IFES have participated. The data was collected through an online questionnaire. The results have identified actions for the removal of attitudinal barriers that are put in motion by a great part of these centers, like the creation and development of awareness programs, speeches and campaigns. It has been noted that the field of Psychology plays one of the main roles on these centers, especially in practices related to educational processes created for those disabled students, favoring the permanence of a still much too rare segment of the population inside the University.
The role of psychologists at the accessibility centers from federal universities of Brazil
Keywords: Accessibility; Psychology; Special Education